The Role of Asceticism in Deification in Cyril of Alexandria’s Festal Letters - Morgan, Jonathan (The Downside review, 2017)
Scholars agree that Cyril of Alexandria is an important patristic proponent of the doctrine of deification. The concept is ubiquitous throughout his writings and often couched in Scriptural phraseology. In his Festal Letters, however, his usual passages of Scripture and the traditional terminology to describe deification are absent. In this essay, I argue that in spite of the dearth of deification language in these letters, Cyril teaches its basic tenets but within a pastoral context that emphasizes the dynamic, practical means of deification through an ascetic lifestyle. While not ignoring the role of divine grace in salvation through the work of Christ and the indwelling Spirit, Cyril stresses that asceticism is an essential means by which deification occurs in believers. This particular emphasis in the Festal Letters brings into focus both Cyril’s concerns as a pastor as well as the synergistic and holistic dynamics of his soteriology.